The Effect of Multiliteracy Learning Model on Critical Thinking Skills Reviewed from Self-Regulation - Mia Nurhidayah; Bambang Sri Anggoro; Fraulein Intan Suri (GAUSS: Jurnal Pendidikan Matematika, 2025)
Abstract As a prospective teacher, it is important for a student to master the 21st century skills, namely the 4Cs. Critical thinking is one of the directions of education in the 21st century. As prospective educators, students need to master critical thinking skills supported by good independent learning as a provision so that they will be able to do meaningful learning in the classroom. This study aims to determine the effect of the application of the multiliteracy learning model on critical thinking skills reviewed from the self-regulation of students. The research uses a quantitative approach, with a type of quasi-experiment design research with a test test research design. Based on the result of the hypothesis test using a two-way ANOVA test with different cells, that is, the result if p−Value ≤0.05 so H0 rejected, but if p−Value >0.05 so H0 Accepted. With the details namely, H0A∶0,000≤0,05 which means H0 rejected, H0B∶0,000≤0,05 which means H0 rejected, and H0AB accepted because of the value p−Value (Sig.) on self-regulation and multiliteracy learning model = 0.374 more than α=0.05 (p−Value (Sig.)>α). Referring to these results, it can be seen that the multiliteracy learning model has an effect on students' critical thinking skills, self-regulation has an effect on students' critical thinking skills, and there is no interaction between the multiliteracy learning model and the level of self-regulation on critical thinking skills. Keywords: Multiliteracy, Critical Thinking Skills, Self-Regulation